Active travel despite motorcar access. A city-wide, GIS-based multilevel study on neighborhood walkability and active travel in Germany - Bödeker, Malte; Finne, Emily; Kerr, Jacqueline; Bucksch, Jens (Journal of transport & health, 2018)
Background - Neighborhood walkability has consistently been associated with utilitarian walking and total physical activity in non-European studies. However, evidence on environmental correlates of physical activity in Europe is still scarce and little is known about potential interactions between neighborhood walkability, active travel, and individual or household related characteristics including available means of transport. - Methods - The study examined the association of neighborhood walkability with self-reported active travel in Bielefeld, Germany. Travel survey data from 2867 adult residents and geographic information for 88 neighborhoods were analyzed in multilevel Poisson regression models including relevant interaction terms to assess potential effect modifications by age, gender, household members, available means of transport, and neighborhood socio-economic status. - Results - Active travel frequencies increased with female gender, available bicycles, neighborhood walkability and decreased with more household members, motorcars, and public transport passes within households. In the final model, a one standard deviation change in neighborhood walkability was associated with an estimated 27.5% increase in active travel trips. Stronger effects were found at younger ages and in participants with greater motorcar availability. No evidence was found for an effect modification by neighborhood socioeconomic status, household members, available public transport passes, or gender. - Conclusions - The positive association between neighborhood walkability and active travel shown in other urban contexts was confirmed in a historically evolved city in Germany. The observed effect varied with respondents’ age and available motorcars, which is in line with recent findings and suggests that public health advocacy in urban planning could promote physical activity on a population level, including those with motorcar access.